STUDI PEMINATAN PENULISAN KREATIF DAN PEMINATAN JURNALISTIK PADA PROGRAM STUDI PENERBITAN - Jimmy Paat (Jurnal Ilmiah Publipreneur, 2014)
The purpose of this research are to (1) provide a reason academic formation of creative writing and journalism concentration, (2) describe the structure of the curriculum design creative writing and journalism concentration, (3) lays out the work prospects of graduates creative writing and journalism concentration, and (4) describe the level of student interest in courses of creative writing and journalism concentration in the department of Publishing in Polimedia. Researcher uses document study to draft a new curriculum structure design creative writing and journalism concentration. Furthermore, to study the interest of students towards creative writing and journalism, he uses a quantitative descriptive research. The results obtained, creative writing and journalism specification need to be held because the two concentrations give much interest to students, needed and in accordance with the development of the science publishing in Indonesia.